Effects of tea plant endophytic phosphate-solubilizing bacteria on the growth and selenium uptake of maize seedlings in selenium-rich soil - Zhang, Shuqing; Guo, Jinmei; Li, Jianfeng; Yang, Yousu; Zhang, Qiuyue (Frontiers in Microbiology, 2025)
Phosphorus (P) is an important nutrient required for plant growth. In this study, seven phosphate-solubilizing bacterial (PSB) strains isolated from tea plant (Camellia sinensis) roots were used as test inoculants. After inoculating maize (Zea mays L.) seedlings for 45 days, we measured the available AN, AP, AK and available Se contents in the rhizosphere soil, as well as the N, P, K, and Se contents in the plants, along with growth and physiological parameters. The study aimed to explore the effects of endophytic PSB from tea plants on maize seedling growth and the uptake of nutrients such as N, P, K, and Se. The results showed that the endophytic PSB enhanced the P content in maize leaves and the AP content in rhizosphere soil. They also significantly increased seedling fresh weight, dry weight, plant height, and root length. Treatment with P. fungorum PMS-05 significantly increased the dry weight, fresh weight, and plant height of seedlings by 103.79, 77.69, and 51.27%, respectively. Inoculation with P. fungorum PMS-20 significantly increased plant height and root length by 70.89 and 223.45%, respectively. Furthermore, treatment with P. fungorum PMS-05 significantly increased the available Se contents in the rhizosphere soil and the plants by 144.47 and 97.77%, respectively. In conclusion, tea plant endophytic PSB can increase the contents of AP and available Se in rhizosphere soil, promote nutrient absorption, and positively impact seedling growth. P. fungorum PMS-05 and P. fungorum PMS-20 showed superior growth-promoting effects on seedlings compared with the other strains tested and can be used to develop high-quality PSB agents tailored for crops grown in selenium-rich red soils in Guizhou.